2019
DOI: 10.1158/2159-8290.cd-18-0903
|View full text |Cite
|
Sign up to set email alerts
|

Single and Dual Targeting of Mutant EGFR with an Allosteric Inhibitor

Abstract: Allosteric kinase inhibitors offer a potentially complementary therapeutic strategy to ATP-competitive kinase inhibitors due to their distinct sites of target binding. In this study, we identify and study a mutant-selective EGFR allosteric inhibitor, JBJ-04-125-02, which as a single agent can inhibit cell proliferation and EGFR L858R/T790M/C797S signaling in vitro and in vivo . However, increased EGFR dimer formation limits treatment effi cacy and leads to drug resistance. Remarkably, osimertinib, an ATP-compe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
243
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 253 publications
(256 citation statements)
references
References 35 publications
(56 reference statements)
11
243
0
2
Order By: Relevance
“…During our PROTACs development process, we identified JBJ‐04‐125‐02 (Figure B), an allosteric inhibitor with a 2‐hydroxy‐5‐fluorophenyl group with improved potency, including the ability to inhibit cell proliferation of Ba/F3 cells as a single agent . Therefore, in addition to DDC‐01‐163, we synthesized and tested JBJ‐04‐125‐02‐based allosteric EGFR degraders.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…During our PROTACs development process, we identified JBJ‐04‐125‐02 (Figure B), an allosteric inhibitor with a 2‐hydroxy‐5‐fluorophenyl group with improved potency, including the ability to inhibit cell proliferation of Ba/F3 cells as a single agent . Therefore, in addition to DDC‐01‐163, we synthesized and tested JBJ‐04‐125‐02‐based allosteric EGFR degraders.…”
Section: Resultsmentioning
confidence: 99%
“…DDC‐01‐163 potently inhibited the proliferation of L858R/T790M mutant EGFR Ba/F3 cells (EC 50 =0.096 μ m ) while sparing the wildtype EGFR Ba/F3 cells (EC 50 >10 μ m ; Figure C and S2). This striking mutant‐selectivity likely arises primarily from the parent allosteric inhibitor scaffold . Interestingly, DDC‐01‐163 was 51‐fold more potent than its parent allosteric EGFR inhibitor, JBJ‐07‐149 (0.096 μ m vs. 4.9 μ m ) in cellular assays, despite being 45‐fold less potent than JBJ‐07‐149 in biochemical assays.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…By targeting the genetic differences of cancer cells, several molecule-targeting drugs, such as Afatinib and Gefitinib, had been approved by U.S. FDA and shown their promising therapeutic activity against various cancers (Cataldo et al, 2011;Hirsch and Bunn, 2012). However, the therapeutic strategies of "one drug-hits-one target-treats-one disease" still face significant challenges as the drug resistance (To et al, 2019;Wojtaszek et al, 2019). Recent studies suggested that targeting the multiple targets might be a practicable approach to ameliorate the therapeutic activity and selectivity, meanwhile preventing the drug resistance (To et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…However, the therapeutic strategies of "one drug-hits-one target-treats-one disease" still face significant challenges as the drug resistance (To et al, 2019;Wojtaszek et al, 2019). Recent studies suggested that targeting the multiple targets might be a practicable approach to ameliorate the therapeutic activity and selectivity, meanwhile preventing the drug resistance (To et al, 2019).…”
Section: Introductionmentioning
confidence: 99%